The Effects of Exposure to Practice Risk on Tax Professionals' Judgements and Recommendations* - Kadous, Kathryn; Magro, Anne M. (Contemporary Accounting Research, 2001)
Tax professionals are responsible for objectively evaluating tax authorities and evidence relevant to their application and for serving as client advocates. We predict that practice risk — that is, exposure to monetary and nonmonetary costs of making inappropriate recommendations — will affect tax professionals' ability to meet these responsibilities by influencing the manner in which they process information about a tax situation as well as their resulting recommendations for clients. We conduct an experiment in which we manipulate practice risk through client characteristics. We also manipulate provision and nature of outcome information. We find that tax professionals process information differently for clients of different risk levels. Specifically, tax professionals weight negative outcome information more heavily when forming likelihood assessments underlying recommendations for a high‐risk client, relative to a low‐risk client. Further, risk directly affects recommendations in that tax professionals more strongly recommend an aggressive position for a low‐risk client. Differential processing of information for clients with identical transactions but different risk levels may protect the tax professional from the higher expected costs of making inappropriate recommendations to high‐risk clients. However, it indicates that tax professionals do not evaluate evidence objectively for all types of clients.